Characteristics of Workers and Description of Hand Eczema as Occupational Dermatitis in the Batik Industry - Zuhaira Nabila; Alya Nasya Nabila; Deska Ayunda Cahyarani; Soffy Aura Putri; Dewinda El F; Dinda Amelia (Takaza Innovatix Labs Ltd., 2026)
Workers exposed to chemicals, allergens, and irritants are at risk of developing occupational skin diseases (OSDs), particularly contact dermatitis or hand eczema. In the batik production process, workers are potentially exposed to batik wax, textile dyes, detergents, solvents, and water, which can increase the risk of skin disorders. This study aims to describe the characteristics of workers and the incidence of hand eczema among batik industry workers. The study used a quantitative method with a descriptive observational design and a cross-sectional approach. The study sample consisted of seven workers selected using a total sampling technique. Data were collected using a structured questionnaire covering respondent characteristics, allergy history, hand eczema history, skin condition, workplace exposure, and use of personal protective equipment. Data analysis was conducted descriptively using frequency distributions and percentages. The results showed that most respondents had no history of hand eczema or complaints of work-related skin diseases. A small number of respondents had a history of eye allergies and a history of itchy rashes on the hands, which are predisposing factors for skin disorders. In addition, most workers did not use protective gloves while working. Although the prevalence of hand eczema in this study was still low, repeated exposure to chemicals still has the potential to increase the risk of occupational skin diseases. Therefore, the implementation of Occupational Safety and Health (K3) programs, the use of personal protective equipment, improving personal hygiene, and education regarding the prevention of skin diseases need to be continuously improved